Production of Omega-3 polyunsaturated fatty acid-enriched chevon using treated oil palm (Elaesis Guineensis Jacq.) frond silage - Ebrahimi, Mahdi (2012)
There is a need to treat oil palm fronds (OPF) to improve its nutritive value and digestibility to be used as small ruminant feed. A study was carried out in which fresh OPF have been ensiled with lactic acid bacteria (LAB), cellulase enzyme and a combination of LAB and cellulase enzyme to improve the fermentation quality and nutrient values of the OPF. The dietary treatment methods comprised non-ensiled fresh OPF (F), ensiled OPF with no additives (C, control), ensiled OPF with a commercial lactic acid bacteria (LAB) inoculant (I), ensiled OPF with an exogenous fibrolytic, cellulase enzyme (E) and ensiled OPF with a LAB inoculant-cellulase combination (I+E). Ensiling was carried out with about 2 Kg samples stored in airtight glass jars at 25-30 oC for 12 wk after which the silage samples were subjected to standard proximate analyses. The ensiling decreased significantly (P < 0.05) the DM concentration of ensiled OPF with additives compared to the non-ensiled fresh OPF and control silage. The LAB inoculant-cellulase combination reduced significantly (P< 0.01) the NDF and ADF content compared to the control silage. Crude fat also decreased significantly (P < 0.05) after ensiling compared to the non-ensiled fresh OPF. All the treated silages had a lower pH (4.09-4.28) than the untreated silage (4.88). Acetic acid and propionic acid in the ensiled OPF were significantly (P < 0.01) higher than the non-ensiled fresh OPF. The NH3-N concentration in the silage with additives significantly decreased (P < 0.01) compared to the non-ensiled fresh OPF and control silage. The LAB inoculant-cellulase combination increased the water soluble carbohydrate (WSC) and ethanol production significantly (P < 0.01) compared to the control silage. The population of LAB increased significantly (P < 0.05) in all treatments with additives compared to the non-ensiled fresh OPF and control silage. The in vitro dry matter digestibility, in sacco dry matter digestibility, in vivo dry matter digestibility, in vitro gas production, in vitro fermentation kinetics and in vivo fermentation kinetics of the silages were determined using rumen fistulated goats. The OPF silage treated with cellulase or the LAB inoculant-cellulase combination showed a significantly (P < 0.01) higher in vitro gas production and dry matter digestibility (DMD) compared to the non-ensiled fresh and control silage. In fact, the in vitro gas production, including maximum gas production and the rate of gas production of the ensiled OPF were all increased by the treatment with either cellulase or the LAB inoculant-cellulase combination. The OPF silage treated with the LAB inoculant-cellulase combination showed significantly higher (P < 0.01) rapidly soluble fractions (18.23%), insoluble but fermentable fractions (43.86%) (P < 0.05) and fractional degradation rates (0.018 h−1) (P < 0.05) than the other treated silages. The in vivo dry matter digestibility of the OPF silage with the LAB inoculant-cellulase combination was 4.12% higher (P < 0.01) than the control silage. Thus, the ensiled OPF treated with the LAB-cellulase combination was selected to be the best treated OPF to be used in the animal feeding trial. Ruminant products are known to contain high saturated fatty acids (SFA) and low polyunsaturated fatty acids (PUFA ), compared to pork, chicken meat or fish. Long chain n-3 PUFA are important in the prevention of modern diseases such as cardiovascular diseases, obesity and cancer. A part of the study attempted to decrease the SFA and increase n-3 PUFA in the chevon using the best treatment of OPF using diets with different n-6: n-3 PUFA ratios. Isonitrogenous and isocaloric experimental diets containing the best treated OPF silage were formulated and either sunflower, palm kernel or linseed oil were used to adjust the dietary n-6: n-3 fatty acid ratios (FAR) to be 2.27:1 (LR), 5.01:1 (MR), and 10.38:1 (HR). Twenty-one five-month old male Boer goats weighing 13.66 ± 1.07 Kg (mean initial body weight ± standard error) were allocated randomly to the three dietary treatment groups and fed for 100 days. The longissimus dorsi (LD) muscle, liver, rumen fluid and rumen digesta were sampled at slaughter. The average daily gain (ADG) for all the experimental groups was similar (P > 0.05). The dressing percentage, back fat thickness and rib eye area of the LR group were significantly (P < 0.05) higher than the HR group. The thiobarbituric acid reactive substance (TBARS) values for the LD muscle for all treatment groups after a 6-day post-mortem aging period were significantly (P < 0.05) higher than at day 1 and the highest TBARS value belonged to the LR group compared to the HR treatment group after a 6-day post-mortem aging period. Goats fed the LR diet had a higher (P < 0.01) concentration (14.55mM/L) of total Increasing the dietary n-6: n-3 FAR lowered (P < 0.01) the concentration of C18:0 but linearly increased (P < 0.01) C16:0, C18:1 trans-11, C18:2n-6, and cis-9 trans-11 CLA in the liver. The LR diet increased significantly (P < 0.01) C18:3n-3, C20:5n-3; C22:5n-3 and C22:6n-3, consequently decreasing the liver n-6: n-3 FAR compared to the HR group. Increasing the dietary n-6: n-3 FAR increased (P < 0.01) the C20:4n-6 while the low n-6: n-3 FAR increased (P < 0.01) @-linolenic acid (C18:3n-3) concentration in the LD muscle. The C20:5n-3, C22:5n-3 and C22:6n-3 showed positive linear effects (P < 0.01) with decreasing the dietary n-6: n-3 FAR. There was a linearly increased population of cellulolytic bacteria including the Ruminococcus albus (P < 0.05) and Ruminococcus flavefaciens (P < 0.05) in the rumen liquid from the LR group compared to the HR group.? ? The? population of Butyrivibrio fibrisolvens was lower (P < 0.05) in the LR group, which had decreased by 31.67%, compared to the HR group. There was a higher (P < 0.05) PPARY? and PPAR? gene expression in the LD muscle for the LR group compared with the HR group, indicating that the low dietary n-6: n-3 FAR upregulated the PPAR? and PPAR? genes. On the contrary, the stearoyl-CoA desaturase (SCD) gene expression showed a significant (P < 0.05) reduction in the LR group compared to the HR group suggesting that the SCD gene was downregulated by the LR dietary treatment. In conclusion, ensiling the OPF with the LAB inoculant-cellulase combination improved the nutritional value and digestibility of the OPF. Diets formulated incorporating the treated OPF and adjusted to have a low dietary n-6: n-3 FAR (2.27:1) did not adversely affect the growth performance of the Boer goats. In fact the VFA in the rumen fluid compared to the HR diet (11.67mM/L).chevon was enriched with higher proportions of the n-3 PUFA. The increased n-3 fatty acids in the rumen fluid, rumen digesta, liver and LD was suggestive of a reduced biohydrogenation possibly due to changes in the ruminal environment which included a lowered pH, increased VFA concentrations and a drastic decrease in the Butyrivibrio fibrisolvens population, the microbe which is actively involved in biohydrogenation in the rumen. The impact of the results derived from this study include the potential reduction in feed costs using the treated OPF as small ruminant feed and the ‘healthier’ omega-3 enriched chevon would be very appealing to the health-conscious consumer.